Assessment of the knowledge level of food handlers in a cookie industry before and after GMP training - Cunha, Luana Maria Meireles; Lima, Consuelo Lúcia Sousa de; Silva, Niara Maria de Jesus (Brazilian Journal of Production Engineering, 2023)
Food handlers play a key role in maintaining food safety and preventing Foodborne Diseases (FBD). Bearing in mind the importance of handlers in the hygienic-sanitary quality of food, this study evaluated the perception and behavior of handlers in a cookie industry in Belém-PA regarding Good Manufacturing Practices (GMP). A questionnaire on Personal GMP Habits was applied, training was carried out on the topics established by current legislation, and audits on personal GMP were also carried out with industry handlers. The handlers’ habits were compared in the period before and after training, in order to verify if the number of nonconformities reduced. 96 food handlers participated in the training, in which it was possible to identify that the handlers already have some knowledge about GMP, however, it was found that, even knowing what the appropriate practices are, their behaviors are not always consistent with the GMP. In relation to the weekly GMP audit, it was possible to observe a significant reduction in the number of non-compliance, mainly regarding large beards. Proving the need for periodic training for the qualification of handlers, with the purpose of contributing to the improvement of the hygienic-sanitary quality of the food offered to consumers.